2014
DOI: 10.3897/zookeys.371.5588
|View full text |Cite
|
Sign up to set email alerts
|

First record of the polychaete Ficopomatus uschakovi (Pillai, 1960) (Annelida, Serpulidae) in the Colombian Caribbean, South America

Abstract: The genus Ficopomatus (Serpulidae) consists of sessile, tubicolous polychaete annelid worms that may colonize a diversity of substrata, and tolerate considerable variations in salinity. Thus, members of this genus, including Ficopomatus uschakovi, in some cases are exotic and maybe invasive. The purpose of our research was to collect and identify marine organisms associated with the submerged roots of mangrove trees in the Gulf of Urabá, Colombian Caribbean, South America. Within the Gulf, there is a well-deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…This exotic polychaete was observed forming conglomerates of calcareous tubes as reported by de Assis et al, (2008) and in sympatry with F. miamiensis. Probably, these two species are competing for food and space on R. mangle roots as was suggested by Arteaga-Flórez et al, (2014).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This exotic polychaete was observed forming conglomerates of calcareous tubes as reported by de Assis et al, (2008) and in sympatry with F. miamiensis. Probably, these two species are competing for food and space on R. mangle roots as was suggested by Arteaga-Flórez et al, (2014).…”
Section: Discussionmentioning
confidence: 96%
“…This species is considered an exotic species, and it was first registered in the Colombian Caribbean by Arteaga-Flórez et al, (2014); given the physicochemical conditions under this species was found, we can consider it as euryhaline and eurythermal. Also, F. uschakovi was found in greater proportions in areas with the lowest percentage of dissolved oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the 1950's, the species has been recorded in the Gulf of Guinea, Western Africa. Recently, it was recorded from eastern Brazil (de Assis et al 2008), Chiapas, the southern Mexican Pacific (Bastida-Zavala & García-Madrigal 2012), Venezuela (Liñero-Arana & Díaz -Díaz 2012) and the Colombian Caribbean (Arteaga-Flórez et al 2014). In this work, the species is recorded in the northern Gulf of Mexico and the U.S. east coast and, likely, has been present since at least 1997 (USNM and SERC, collection data).…”
Section: Non-indigenous Speciesmentioning
confidence: 99%